Alih Kode dan Campur Kode sebagai Strategi Retoris dan Identitas Religius dalam Ceramah KH. Muhammad Ridlo di Majelis Taklim Al-Malikiy - Ahmad 'Aizar Al Ahdaly; Umi Kulsum; Minatur Rokhim; Naufal Syafiq Wilfa; Bismi Azka (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to describe the phenomenon of code-switching and code-mixing in religious sermons delivered after Ratib activities at Majelis Taklim Al Malikiy. The focus of this research is on language use as a medium for conveying religious messages and as a marker of religious identity in a non-formal religious context. This study employs a descriptive qualitative approach, with data consisting of the preacher’s utterances collected during Ratib activities. Data were collected through observation and note-taking and carefully transcribed to preserve the original context of the utterances. The results indicate that code-switching occurs when the preacher shifts from Indonesian to Arabic to adjust meanings to religious contexts and to emphasize certain messages. Meanwhile, code-mixing appears as the insertion of Arabic words, phrases, and expressions into Indonesian utterances, which serves to strengthen religious nuance and build emotional closeness with the audience. Overall, this study shows that code-switching and code-mixing function not merely as linguistic phenomena, but also as rhetorical strategies in religious preaching. Language plays an important role in constructing meaning, reinforcing religious identity, and enhancing the effectiveness of dakwah in non-formal religious settings.